Performance of OFDM in Time Selective Multipath Fading Channel in 4G Systems - Dixit, Saurabh; Katiyar, Himanshu (2015 Fifth International Conference on Communication Systems and Network Technologies, 2015)
With the growing demand for higher data rate networks, OFDM has emerged as a key technology for 4G standards like 3GPP LTE, IEEE 802.16m WiMAX and IEEE 802.11n WLAN. With its robustness to frequency selective fading, high spectral efficiency and ease of implementation by means of Discrete Fourier Transform(DFT), OFDM is a cutting edge technology for Broadband mobile wireless. Along with its compatibility with MIMO, OFDM is an attractive air-interface solution to meet the demands of 4G networks. In mobile environment, channel is subject to both time and frequency selective fading. Although OFDM is resistant to ISI resulting from frequency selective fades, but it is quite sensitive to time selective multipath fading. This time selective fading causes ICI thus degrading system performance. For a satisfactory performance of OFDM, it is imperative that the sub-carriers remain orthogonal to each other. The orthogonal behaviour of sub-carriers can be jeopardised due to two effects namely Carrier frequency offset, and Doppler spread. In the case of high Doppler spread owing to high mobility, maintaining orthogonality between sub-carriers is a challenging task. To keep a SIR of 20 dB, OFDM symbol duration must not exceed 8% of the Coherence time of the channel. In the case of Carrier frequency offset, which is caused by the use of Local Oscillators, there is a frequency shift of the received signal spectrum. This frequency shift of the received signal spectrum compromises the orthogonality between the sub-carriers. This paper reviews the methods to mitigate the deleterious effect of time selective fading and compares the simulation result of high Doppler spread with that of small Doppler spread.